Rationalization Of Medication Use In Non-Specific Diarrhea, Non-Pneumonia Ari, And Myalgia In North Gorontalo 2023 - Nilamsari, Putri; Emelda, Andi; Yuliana, Dewi (Sekolah Tinggi Agama Islam Kuningan, 2024)
Rational drug use ensures medication is prescribed based on clinical needs in appropriate quantities. However, irrational drug use remains common, including incorrect indications, improper dosages, and administration errors. This study aims to evaluate the rationality of antibiotic use for non-specific diarrhea, non-pneumonia ARI, and myalgia in North Gorontalo Regency, Gorontalo Province, in 2023. Using a descriptive observational cross-sectional design, data were collected retrospectively from patient prescriptions and medical records. Findings indicate that the average number of drugs per prescription sheet at North Gorontalo District Health Centers exceeds WHO’s recommended standard of 1.8–2.2 items. While antibiotic and injection drug use generally aligns with WHO indicators, some centers exceeded recommended levels in certain months. Excessive drug prescriptions pose polypharmacy risks, while overuse of antibiotics may contribute to resistance. Overall, antibiotic use for non-specific diarrhea and non-pneumonia ARI, as well as injection drug use for myalgia, is largely rational, though occasional deviations from WHO guidelines were observed.